Educational and pedagogical challenges in the Arab world - Medjahed, Abdenacer (The International tax journal, 2025)
Nations that are educationally and pedagogically backwards are, by necessity, socially, culturally, economically, and civilisationally backwards, and their morals are in decline. Since morality is one of the fundamental pillars of building and advancing nations, education constitutes the principal means of teaching morals, rooting them deeply, and applying them within the conduct of both the individual and the community. Moreover, it stands as one of the essential foundations of construction, renaissance, and civilisation. Indeed, morality is inseparable from education because, through education, humankind has transmitted ethics, values, knowledge, art, law, and culture throughout history. A revolution in education must accompany a cultural, moral, and economic renaissance in the Arab world. As we plan to reform education and pedagogy in our countries, we must design a project that clearly defines the ultimate purpose of education, the means and methods enabling us to attain that purpose, and the foundational basis for the reform process while establishing the vision, mechanism, tools, and methodology. The foundation of renaissance, development, and progress in any nation is not merely economic growth and military strength but, above all, education and pedagogy.